The value of drip versus spray cooling at two flow rates to reduce heat stress of finishing swine - David A Nichols; R C Thaler; James P Murphy; Robert H Hines; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1987)
One hundred fifty pigs were used to evaluate the effectiveness of either spray cooling or drip sprinkling to reduce heat stress in finishing swine. In addition, water flow rates of .2 gal/pig/hr and .4 gal/pig/hr were compared. All wetting treatments significantly (P<.01) improved average daily gain and feed intake (P<.05) compared with non-wetted control. No differences were observed in feed to gain ratio among treatments. Drip sprinkling at the higher flow rate resulted in performance equal to that with intermittent spray cooling at both flow rates.; Swine Day, Manhattan, KS, November 19, 1987
Keywords: Swine day; 1987; Kansas Agricultural Experiment Station contribution; no. 88-125-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 528; Swine; Drip vs. spray cooling; Heat stress; Finishing swine